2011
DOI: 10.1111/j.1442-1984.2011.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral color variation and associations with fitness‐related traits inMalva moschata(Malvaceae)

Abstract: Genetic polymorphisms for floral color are interesting phenomena to study because they are likely to be maintained by opposing selective forces. Pollinator preferences may exert direct selection on floral color; however, floral color might also be the indirect target of selection through genetic associations with other traits under selection. Malva moschata (Malvaceae) is a North American species that produces either red or white flowers. In the present study, we present reflectance spectrophotometry data that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Nectar nicotine levels were not correlated with any other measured floral trait such as nectar volume, nectar sugar concentration or emission of benzylacetone, the main floral attractant. These results are consistent with other studies that have found that floral traits evolve independently of each other in response to different floral visitors (Mazer and Hultgard, 1993; Frey et al. , 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Nectar nicotine levels were not correlated with any other measured floral trait such as nectar volume, nectar sugar concentration or emission of benzylacetone, the main floral attractant. These results are consistent with other studies that have found that floral traits evolve independently of each other in response to different floral visitors (Mazer and Hultgard, 1993; Frey et al. , 2011).…”
Section: Discussionsupporting
confidence: 93%
“…However, such interspecific comparisons are less useful when used to infer the processes underlying pollinator shifts by two reasons: (i) the a priori choice of exclusively bee-or hummingbird-pollinated species and (ii) the impossibility to isolate a single target trait from other interspecific/intraspecific floral variations. In this sense, a discrete intraspecific variation allows the discrimination of a specific trait function, simultaneously controlling for other trait variations (Medel, Botto-Mahan & Kalin-Arroyo 2003;Frey, Dunton & Garland 2011). Moreover, there is evidence supporting pollinator indifference or preference for intraspecific variation of floral traits (Waser & Price 1981;Goulson & Wright 1998;Medel, Botto-Mahan & Kalin-Arroyo 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement covers 250 to 750 nm using 0.38-nm increments. We only measured reflectance pattern per petal since there should be no difference within the same petal but there may be some differences among plants (Frey et al 2011). In total, we took one measure per petal, per flower from a total of 38 flowers sampled from 10 randomly selected individuals (2-4 flowers per individual).…”
Section: Floral Color and Scentmentioning
confidence: 99%
“…Additionally, the red flower color of R. protistum var. giganteum might not only provide a strong signal for bird pollination, but also attract bumblebees as exemplified in Malva moschata whose red flower individuals get more visitation of bumblebees than white flower plants (Frey et al 2011) and R. cynocarpum whose flower visitors are mostly bumblebees, accounting for 90% of total visits (Ma et al 2014).…”
Section: Floral Traits and Potential Pollinatorsmentioning
confidence: 99%